Mysql Database Processing Information System Using The System Development Life Cycle (SDLC) Method At Quality Guarantee Agency Working Unit At National University: Mysql Database Processing Information System Using The System Development Life Cycle (SDLC) Method At Quality Guarantee Agency Working Unit At National University - Achmad Faqihuddin; Iwan Wahyuddin; Novi Dian Nathasia (Jurnal Mantik, 2020)
The National University Quality Assurance Agency (BPM) is a form of quality assurance organization at the National University to guarantee the fulfilment of quality standards in the management of education, research and community service. However, the database system at BPM is not sufficient enough to do the data processing that is needed, namely where BPM does not have master data yet. Therefore, a database system design is needed so that BPM has its own system to facilitate the processing of data in each unit, and later each unit is able to upload the regulations made based on access to the Quality Assurance Unit (UPM) itself. In managing this data MySQL database software and PHP programming language are used for the server idea. The purpose of building a database system at BPM is so that data processing of existing regulations can be more flexible and efficient.